SPECIFIC FEATURES OF GREEN ECONOMY REFORM IN OUR REPUBLIC - Rasulova Mukhabat Tishabayevna (Journals Park Publishing, 2025)
The article provides information on the formation of a "green" economy, stimulating "green" growth and development.
Keywords: Sustainable development, green economy, green growth, eco-innovation, new development model, low-carbon economy, sustainable development goals.